Answer :

Answer:

0=x²+12x−69 Subtract x² from both sides. −x²=12x−69 Subtract 12x from both sides. −x²−12x=−69 Divide both sides by -1. x²+12x=69 Add (12/2)^2=36 to both sides to complete the square.

hope it helps

please marl brainliest

The required function completing the square is ( x + 6 )² = 105.

To rewrite the function by completing the square f(x) = x² + 12x - 69​.

What is What are functions?

Functions are the relationship between sets of values. e g y=f(x), for every value of x there is its exists in a set of y. x is the independent variable while Y is the dependent variable.


Function f(x) = x² + 12x - 69​
In order to find the perfect square of the function.
f(x) = 0
x² + 12x - 69​ = 0
Half the coefficient of x  
coefficient of x = 12
=12/2= 6
Add and subtract the square of it in the equation
6² = 36
x² + 12x - 69​ +36 -36 = 0
Rearrange,
x² + 12x +36 =69+36
x² + 6x + 6x +36 =105
x( x + 6 ) + 6 ( x + 6) =105
(x+6)(x+6) = 105
(x+6)² = 105

Thus, The required function completing the square is ( x + 6 )² = 105.

Learn more about function here:

brainly.com/question/21145944

#SPJ2

Other Questions